ANALISIS USAHATANI DAN DINAMIKA PEMANFAATAN LAHAN PADI LADANG DI KAMPUNG TANJUNG SARI KECAMATAN BONGAN KABUPATEN KUTAI BARAT - Nike Widuri (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This study aims to research of analysis farming and utilization dynamics of paddy field in village Tanjung Sari of Bongan Regency. Research carried out for three months starting from February 2015 to June 2015 in the village Tanjung Sari of Bongan Regency. This study used production analysis to know about revenue, total cost and R/C ratio of flat farmer and then used multiple linier regression analysis in discuss about of effect between income with seeds, fertilizer , pestiside, labor. Beside that to disscuss of utilization dynamics of paddy field with description hectarage which owned by farmers from 2004 until 2014. Wherein location determination is done deliberately called purposive sampling called purposive sampling. The result showed that average revenue of farmers is Rp 10.244.000 and income of farmers is Rp. 8.248.677. While farmers income earned Rp. 8.248.677. With return cost ratio was 5.04. It means that the paddy field of farming give much benefit to the farmers. For that factors that significantly as fertilizer and labor. While the seeds and insectisicider had no significant effect. Land used made by farmers in order to increase farmers income. Therefore from year to year area used by farmers in line with result obtained production.